2023
DOI: 10.3390/buildings13030737
|View full text |Cite
|
Sign up to set email alerts
|

An Information Management Model for Addressing Residents’ Complaints through Artificial Intelligence Techniques

Abstract: Construction companies usually record customer complaints as unstructured texts, resulting in unsuitable information to understand defect occurrences. Moreover, complaint databases are often manually classified, which is time-consuming and error-prone. However, previous studies have not provided guidance on how to improve customer complaint data collection and analysis. This research aims to devise an information management model for customer complaints in residential projects. Using Design Science Research, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Tests indicated that the SCMS can streamline complaint handling, offering customers more avenues to file complaints and track their status. Focused on the construction sector, a research paper highlights the challenges of managing customer complaints recorded as unstructured texts 4 . The authors used Natural Language Processing (NLP) to develop a word menu for lodging complaints and proposed a recommendation system based on machine learning.…”
Section: Methodology and Findings From Recent Researchmentioning
confidence: 99%
“…Tests indicated that the SCMS can streamline complaint handling, offering customers more avenues to file complaints and track their status. Focused on the construction sector, a research paper highlights the challenges of managing customer complaints recorded as unstructured texts 4 . The authors used Natural Language Processing (NLP) to develop a word menu for lodging complaints and proposed a recommendation system based on machine learning.…”
Section: Methodology and Findings From Recent Researchmentioning
confidence: 99%
“…The communication quality of wired intercom systems remains constant, in contrast to wireless systems that are susceptible to interference and signal degradation. When it's critical to keep sensitive information safe and ensure that data remains accurate, wired intercoms are the way to go [7].…”
Section: ░ 2 Related Workmentioning
confidence: 99%
“…Given that the construction companies carrying out the repairs often fall short of satisfying the occupants' requirements and/or expectations, to improve occupant satisfaction it is essential to identify occupant requirements and/or expectations in detail prior to carrying out the repairs. As a preliminary step in this direction, Bazzan et al [22] proposed an information management model that provides a structured database in which to store text-based resident complaints efficiently and effectively using artificial intelligence techniques. With respect to building maintenance management, a number of studies have taken the approach of examining occupant complaints and satisfaction as the basis for improving building performance strategies (e.g., heating, cooling, and elevators) and indoor environment quality in accordance with the results of interviews, text mining, and neural network analysis [9,16,[23][24][25].…”
Section: Literature Review 21 Related Work On Occupant Satisfaction A...mentioning
confidence: 99%